The Role of Bronchoscopy for Successful Removal of A Chronic Aspirated Foreign Body After Twenty Years - Haris, Abdul; Parsama Putra, Ngakan Putu (Malang Respiratory Journal, 2021)
Title: The Role of Bronchoscopy for Successful Removal of A Chronic Aspirated Foreign Body After Twenty YearsAuthor: Abdul Haris, MD. Pulmonology and Respiratory Medicine Department, Brawijaya University, Malang, Indonesia. Supervisor: Ngakan Putu Parsama Putra, MD, Pulmonologist Consultant, Introduction:. A Man with complaints of chronic cough, and shortness of breath, with history of inhaled metal bullet 20 years ago. Chest x-ray thorax revealed a foreign body and pleural effusion.Case Description: Patient is a 58 years old male with complaints chronic cough and shortness breath, he had inhaled  metal bullet in 20 years ago. Chest x ray revealed a foreign body and pleural effusion dextra. Fiber optic bronchoscopy shon corpus alienum metal bullet in medial lobus dextra, and its was retrieved using basket forcepDiscussion: the diagnosis of foreign body aspiration as some patients may not offer a clear history of aspiration or may present late. In addition, malignancy, lung tuberculosis, chronic pneumonia can be misdiagnosed to patients, fiber optic bronchoscopy has been secure and effective procedure in the therapy of foreign body in the airway